2020
DOI: 10.1097/gox.0000000000002831
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis for In-house versus Industry-printed Skull Models for Acute Midfacial Fractures

Abstract: Background: Industry-printed (IP) 3-dimensional (3D) models are commonly used for secondary midfacial reconstructive cases but not for acute cases due to their high cost and long turnaround time. We have begun using in-house (IH) printed models for complex unilateral midface trauma. We hypothesized that IH models would decrease cost and turnaround time, compared with IP models. Methods: We retrospectively examined cost and turnaround time data from midface trauma cases perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…It has previously been shown that an office-based 3D printing workflow demonstrated improvements in operating room efficiency and cost-effectiveness, with satisfactory patient safety and outcomes in mandibular fractures. 2,5 In this study, we report a similar workflow in successfully repairing orbital fractures.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has previously been shown that an office-based 3D printing workflow demonstrated improvements in operating room efficiency and cost-effectiveness, with satisfactory patient safety and outcomes in mandibular fractures. 2,5 In this study, we report a similar workflow in successfully repairing orbital fractures.…”
Section: Discussionmentioning
confidence: 94%
“…Disadvantages of in-house 3D printing have been the material costs associated with obtaining and using a 3D printer, the lack of experience and/or guidance in utilizing the software required to print the 3D models, and regulations for clinical application 4 . Consequently, patient-specific implant (PSI) models often rely on outsourcing to various vendors, which can add cost and delay fracture repair 5 …”
mentioning
confidence: 99%
“…Centres utilising 3D printing must take into account not only the cost of the physical printer but also the printing materials themselves [31]. A 2020 study evaluated the cost of in-house printing of mandibular models in facial trauma to be $1677.82/patient [32].…”
Section: Consideration Of Costmentioning
confidence: 99%
“…The cost breakdown of printing in-house came out to be $34.50 for software and disposable fees, $43.80 for segmentation, $11 for materials, $65.60 for print time fees, and $20.50 for production. 40 Thus, printing at the point-of-care can further decrease the cost of PSIs and increase their availability to patients.…”
Section: Vsp and 3d Printing In Reconstruction Of Orbital Fracturesmentioning
confidence: 99%